Altered Ca(2+) sparks in aging skeletal and cardiac muscle - Weisleder, Noah (2008)
Ca(2+) sparks are the fundamental units that comprise Ca(2+)-induced Ca(2+) release (CICR) in striated muscle cells. In cardiac muscle, spontaneous Ca(2+) sparks underlie the rhythmic CICR activity during heart contraction. In skeletal muscle, Ca(2+) sparks remain quiescent during the resting state and are activated in a plastic fashion to accommodate various levels of stress. With aging, the plastic Ca(2+) spark signal becomes static in skeletal muscle, whereas loss of CICR control leads to leaky Ca(2+) spark activity in aged cardiomyocytes. Ca(2+) spark responses reflect the integrated function of the intracellular Ca(2+) regulatory machinery centered around the triad or dyad junctional complexes of striated muscles, which harbor the principal molecular players of excitation-contraction coupling. This review highlights the contribution of age-related modification of the Ca(2+) release machinery and the effect of membrane structure and membrane cross-talk on the altered Ca(2+) spark signaling during aging of striated muscles.